2022
DOI: 10.1088/1361-648x/ac7f16
|View full text |Cite
|
Sign up to set email alerts
|

Cr2XTe4 (X = Si, Ge) monolayers: a new type of two-dimensional high-T C Ising ferromagnetic semiconductors with a large magnetic anisotropy

Abstract: Two-dimensional (2D) ferromagnetic semiconductor (FMS) provides the ideal platform for the development of quantum information technology in nanoscale devices. However, most of them suffer from low Curie temperature and small magnetic anisotropic energy (MAE), severely limiting their practical application. In this work, by using first-principles calculations, we predicted two stable 2D materials, namely, Cr2SiTe4 and Cr2GeTe4 monolayers. Interestingly, both of them are intrinsic direct band gap FMSs (∼1 eV) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…2 This broke the stranglehold of the Mermin-Wagner theorem, 3 which indicated that long-range magnetic ordering was strictly forbidden in low-dimensional materials. For lowdimensional materials, magnetism can be regulated by various measures, such as an external electric field, 4,5 strain and stress engineering, [6][7][8] edge modification, 9 surface adsorption, [10][11][12] transition-metal atom doping, [13][14][15] defect engineering 16,17 and carrier doping. [18][19][20] In fact, carrier doping is always the most appropriate method to induce itinerant ferromagnetism, con-forming to Stoner's criterion.…”
Section: Introductionmentioning
confidence: 99%
“…2 This broke the stranglehold of the Mermin-Wagner theorem, 3 which indicated that long-range magnetic ordering was strictly forbidden in low-dimensional materials. For lowdimensional materials, magnetism can be regulated by various measures, such as an external electric field, 4,5 strain and stress engineering, [6][7][8] edge modification, 9 surface adsorption, [10][11][12] transition-metal atom doping, [13][14][15] defect engineering 16,17 and carrier doping. [18][19][20] In fact, carrier doping is always the most appropriate method to induce itinerant ferromagnetism, con-forming to Stoner's criterion.…”
Section: Introductionmentioning
confidence: 99%
“…), the valence band maximum (VBM) and conduction band minimum (CBM) are contributed by B-p z /Co-d xy and B-p z /Co-d xz electrons (Figure 3G).It is demonstrated that the magnetocrystalline anisotropy can break the symmetry in 2D magnetic materials, which can effectively stabilize the long-range magnetic ordering[49][50][51]. Magnetic anisotropic energy (MAE) value is defined as the largest energy between magnetization of the magnetic easy axis and hard axis, which can be used to weight the spin flipping difficulty.…”
mentioning
confidence: 95%
“…[6][7][8][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Further analysis shows that magnetic anisotropy (MA) is the prerequisite and foundation to verify whether a 2D material exhibits a magnetically ordered phase above zero temperature, [28][29][30] and the 2D FM order can be stabilized by the magnon excitation gap caused by uniaxial magnetic anisotropy. [31][32][33] MA, which can be scaled by the magnetic anisotropy energy (MAE), is mainly determined by two factors; one is the magnetocrystalline anisotropy resulting from the spin-orbit coupling interaction (SOC-MAE) and the other is the shape anisotropy caused by the dipole-dipole interaction (shape-MAE). 34 Compared with the SOC-MAE, the shape-MAE is often relatively weak and of less concern.…”
Section: Introductionmentioning
confidence: 99%